Neurodevelopment in school‐aged children after intrauterine exposure to antipsychotics. (10th November 2022) - Schrijver, Lisanne; Robakis, Thalia K.; Kamperman, Astrid M.; Bijma, Hilmar; Honig, Adriaan; van Kamp, Inge L.; Hoogendijk, Witte J. G.; Bergink, Veerle; Poels, Eline M. P.
Abstract: Objective: Antipsychotics are increasingly prescribed in pregnancy, yet little is known about potential long‐term developmental effects on children. In this study, we investigated the effect of prenatal antipsychotic exposure on neurodevelopmental functioning in school‐aged children. Methods: We performed a cross‐sectional neurodevelopmental assessment of 91 children aged 6–14 years whose mothers had severe mental illness and were either exposed or unexposed to antipsychotic medication during pregnancy. Neurodevelopmental outcomes were assessed using validated neurodevelopmental assessment instruments to examine the child's IQ and global cognitive functioning, and the presence of any psychiatric disorders and/or learning problems in the child was assessed by parental report. Results: No statistically significant associations were found between antipsychotic exposure during pregnancy and either adverse neurodevelopmental outcomes (IQ, neuropsychological function), likelihood of psychiatric diagnosis, or learning problems based on parental report. Analyses were likely limited in power to detect subtler differences in neurodevelopmental functioning because of small sample size and heterogeneity of the sample. Conclusions: In this exploratory cohort study, intrauterine exposure to antipsychotics was not associated with any adverse effect on IQ or neurodevelopmental functioning in a cohort of school‐aged children (6–14 years).